THE EFFECT OF WORK STRESS AND WORK CULTURE ON EMPLOYEE PERFORMANCE AT THE REGIONAL REVENUE AGENCY (BAPENDA) OF PANGKEP REGENCY - Sappara, Sudirman; Nur, Muh Fajar (Journal of Entrepreneur, Business and Management, 2023)
This research aims to investigate the influence of work stress and work culture on employee performance. In this study, an analysis of three main hypotheses was carried out: the influence of work stress on performance, the influence of work culture on performance, and the combined influence of work stress and work culture on performance. The results of the analysis show that work stress has a significant influence on employee performance, with a significance value of 0.021. Meanwhile, work culture does not show a significant influence on performance, as evidenced by a significance value of 0.637. However, when work stress and work culture are analyzed simultaneously, both show a significant influence on employee performance, with a significance value that is as significant as the analysis of work stress individually. These findings emphasize the importance of considering the interaction between work stress and work culture in influencing employee performance. This study provides new insights for organizational management in designing strategies to improve employee performance, taking into account stress factors and work culture. Keywords: Work Stress, Work Culture and Employee Performance